دور إدارة المعرفة في مؤسسات التعليم العالي في ضمان جودة الخدمات التعليمية والإدارية (دراسة تطبيقية على الجامعة العربية الخاصة) - ديوب أيمن; العلي رامي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The present study aimed to provide an intellectual and practical framework for the application of the concept of knowledge management and its impact on the quality of educational and administrative services in the institutions of higher education in general and the Arab Private University in particular, based on theoretical and survey studies in different parts of the world, and the study of the Arab Private University as an practical example performs knowledge management operations and their impact on the quality of educational and administrative services. A theoretical background was presented to the subject, during which the basic concepts of knowledge management were discussed and reviewed including the definition of “knowledge” concept, types of knowledge, the concept of “knowledge management” and knowledge management objectives. This was followed by a discussion of the concept of quality in educational services and the important dimensions of the application of knowledge management in institutions of higher education and its impact on the quality of educational and administrative services. The researcher studied knowledge management importance and applications in the Arab Private University, based on the pillars of the University’s vision, objectives, organizational structure and infrastructure. And then examine the role of these applications in ensuring the quality of scientific research services, teaching and curriculum, administrative services, and the extent to which the center for professional development of quality in the university. The researcher used the questionnaire tool to study the role of knowledge management application on the quality of educational and administrative services. The researcher found a positive correlation between the independent variable of knowledge management and the dependent variable of quality of educational and administrative services. استهدفت الدراسة الحالية تقديم إطار فكري وتطبيقي لتطبيق مفهوم إدارة المعرفة ودوره في جودة الخدمات التعليمية والإدارية في مؤسسات التعليم العالي بشكل عام والجامعة العربية الخاصة بشكل خاص، مبنياً على الدراسات النظرية والمسحية في أنحاء متفرقة من العالم، ودراسة الجامعة العربية الخاصة كمثال تطبيقي يقوم بعمليات إدارة المعرفة ودورها في ضمان جودة الخدمات التعليمية والإدارية. تم تقديم خلفية نظرية للموضوع تضمنت مناقشة واستعراض المفاهيم الأساسية لإدارة المعرفة والتي شملت: التعريف بمفهوم المعرفة وأنواعها، ومفهوم إدارة المعرفة, وأهداف إدارة المعرفة، والفوائد المتحققة لمنظمات التعليم العالي من تطبيق إدارة المعرفة. وتلا ذلك مناقشة مفهوم الجودة في الخدمات التعليمية والإدارية والأبعاد المهمة لتطبيق إدارة المعرفة في مؤسسات التعليم العالي ودورها في ضمان جودة الخدمات التعليمية والإدارية. قام الباحث بدراسة أهمية وتطبيقات إدارة المعرفة في الجامعة العربية الخاصة استناداً إلى ركائز رؤية الجامعة وأهدافها وهيكلها التنظيمي وبنيتها التحتية لإدارة المعرفة, ومن ثم دراسة دور هذه التطبيقات في ضمان جودة خدمات البحث العلمي, والتدريس والمناهج, والخدمات الإدارية, ومدى تحقيق مركز التطوير المهني للجودة في الجامعة المذكورة. استخدم الباحث أداة الاستبيان لدراسة دور تطبيقات إدارة المعرفة على جودة الخدمات التعليمية والإدارية, وتبين له وجود علاقة ارتباط إيجابية بين المتغير المستقل المتمثل بإدارة المعرفة والمتغير التابع المتمثل بجودة الخدمات التعليمية والإدارية.